Minimally Invasive Two-Staged Surgery in the Treatment of Large Cystic Lesions of the Jaw - Andreea Irimia (MDPI AG, 2021)
Background: Cystic lesions of the jaw are commonly found in clinical practice. Large, expansive cysts raise challenges for the clinician from both diagnostic and surgical perspectives. The aim of our work is to present a combined, two-staged surgical approach in histologically confirmed non-aggressive cystic lesions of the jaw. Methods and Results: We report the case of an extensive mandibular cyst, associating a high risk of bone fracture, that is treated in the initial stage by cystic decompression through marsupialization with concomitant histological diagnostic confirmation, followed in the second stage by radical excision and mandibular reconstruction with titanium mesh, with the purpose of prevention for oro-cystic chronic fistula formation. Conclusions: Large odontogenic mandibular cysts imply a meticulously conducted assessment and treatment. Marsupialization should be taken into consideration for the treatment of large cystic lesions, followed by secondary enucleation, with minimal risks for the patient. The soft tissue healing process can be optimized with the use of titanium meshes, as an alternative for other reconstructive techniques, in the management of large cystic lesions.